Method for preparing molybdenum-copper composite material based on additive manufacturing
By using electron beam selection melting technology and additive manufacturing technology in the preparation of molybdenum-copper composites, the density and composition uniformity of molybdenum-copper composites are solved, and efficient preparation of molybdenum-copper composites is achieved, which simplifies the process flow and Improved material properties.
Patent Information
- Application Number
- CN202411525797.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2024-12-17
AI Technical Summary
In the existing preparation methods of molybdenum-copper composite materials, there are problems such as uneven copper phase melting and penetration, low material density and cumbersome processing procedures.
Pure copper powder and molybdenum powder are mixed in proportion, and after grinding and granulation, combined with electron beam selection melting technology (SEBM), molybdenum-copper composite material is prepared. Through presintering and electron beam remelting additive manufacturing technology, it is melted and printed layer by layer. Finally, Perform sandblasting treatment to remove excess metal materials.
The high density (up to 99.7%) and uniform component distribution of molybdenum-copper composite materials are achieved, the process flow is simplified, and the thermal conductivity and comprehensive performance of the material are improved.
Smart Images

Figure CN119140842A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal-based composite materials and relates to a method for preparing a molybdenum-copper composite material based on additive manufacturing. Background Art
[0002] In recent years, electronic technology has developed rapidly in the direction of high power, integration, and miniaturization, greatly improving the working performance of electronic products. However, the pursuit of performance in the use of electronic products will also lead to an increase in the power density of electronic components, a sharp increase in the heat generated, and ultimately affect the working efficiency and service life of electronic products. How to effectively improve the heat dissipation performance of electronic products has become a research hotspot in the field of electronic technology. Among them, thermal management materials are an important part of the heat dissipation mechanism of electronic components and play a decisive role in improving the heat dissipation performance of electronic products.
[0003] At present, there are many types of thermal management materials for electronic products on the market, among which copper-based composite materials are one of the most important components of thermal management materials. Molybdenum-copper composite materials are high-performance heat dissipation materials with good processing performance developed on the basis of Cu-based alloys. They combine the high thermal conductivity of Cu and the low expansion of Mo. By changing the components of Mo-Cu pseudoalloys to adjust the thermal expansion coefficient, thermal conductivity and other physical properties, different thermal management or heat dissipation requirements can be met.
[0004] Since the melting points of Mo and Cu are very different and they are neither solid-soluble nor can form intermetallic compounds, the common metal melting and mixing processing method cannot be carried out. For the preparation of molybdenum-copper composite materials, the preparation methods currently used include: gel injection molding-melt infiltration method, gel-co-reduction method, thermochemical-flame spraying technology, laser rapid prototyping technology, etc. Duan Bohua et al. proposed to use gel injection molding-melt infiltration method to prepare Mo-Cu alloy. First, Mo gel green body is made by gel injection molding, and then a porous Mo skeleton is obtained by drying, degreasing and other treatments. Finally, copper infiltration treatment is performed to obtain Mo-Cu composite body, and its expansion coefficient (100°C) reaches 6.357×10 −6 / °C; Chen Jigui et al. prepared ultrafine Mo-Cu powder by gel-co-reduction method with (NH4)6Mo7O 24·4H2O and CuO are used as precursors, and a dry gel is prepared by an organic-assisted gel process. The gel is calcined and reduced to obtain a Mo-Cu composite powder with a Cu content of 20% (mass fraction). The relative density of the formed compact can reach 99.65% after sintering in a H2 atmosphere at 1150°C for 90 minutes, and the grains of the sintered body are fine and uniform, and it has good physical and mechanical properties; The Chinese invention patent with an application date of November 16, 2022 and a publication number of CN115710683A discloses a thermochemical method and a flame spraying method for preparing a Mo-Cu alloy, wherein ammonium tetramolybdate and copper nitrate powder are mixed, ammonia water and deionized water are added for stirring, and the product is calcined to obtain a Mo-Cu composite powder coated with Cu, and the powder is sprayed onto the surface of the substrate by oxygen-acetylene flame spraying technology, and multi-layer spraying is performed. Mo-Cu alloy was obtained by coating, and the density of its products could reach more than 98% after hydrogen reduction and vacuum sintering; Bai Peikang et al. used high-purity ultrafine molybdenum powder as raw material, fine hot melt adhesive prepared with polyvinyl acetate and a small amount of wetting agent as medium, and obtained coated Mo powder by high-speed stirring, low-temperature crushing and screening. The coated Mo powder was printed into parts by laser, and the formed samples were degreased and pre-sintered. Finally, the pre-sintered samples were copper-infiltrated. The results showed that Mo and Cu in the copper-infiltrated parts were closely connected, Mo and Cu were cross-distributed, the tensile strength was 480~490Mpa, the elongation was 12.1%~12.7%, and the impact toughness was 14.1~14.8KJ / m 2 ; The Chinese invention patent with application date of November 23, 2020 and publication number CN112708882A discloses a method for high-speed laser cladding of Mo-Cu alloy layer on Cu substrate. Molybdenum and copper powders are delivered simultaneously, and three layers of Mo-Cu alloy layers are clad on the surface of copper substrate. The mass ratio of molybdenum to copper in the first layer is 2:3, and the cladding power is 3500W; the second layer is 3:4, and the power is 3300W; the third layer is 1:1, and the power is 3000W. The obtained Mo-Cu alloy layer has uniform composition and structure, no obvious cracks, good bonding between the coating and the substrate, and between the coatings. The hardness of the outermost layer of Mo-Cu alloy layer can reach 500HV, and the hardness of the copper substrate / cladding interface is 120HV. Although the above technologies can all produce Mo-Cu composite materials, the materials cannot avoid the problems of uneven copper phase infiltration, complicated processing procedures, and low material density of the molybdenum-copper composite materials. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a molybdenum-copper composite material based on additive manufacturing, in which pure copper powder and molybdenum powder are mixed and granulated in proportion, and the molybdenum-copper composite material is prepared in combination with electron beam selected area melting technology (SEBM), thereby solving the problems of uneven copper phase infiltration, low material density and complicated processing flow existing in the molybdenum-copper composite material prepared by the existing method.
[0006] The technical solution adopted by the present invention is a method for preparing a molybdenum-copper composite material based on additive manufacturing, and the specific steps are as follows: S1, mixing electrolytic pure copper and pure molybdenum powder to obtain mixed powder; S2, grinding the mixed powder with grinding balls for 2-5 hours to obtain ground powder; S3, sprinkle the ground powder from a height above the disc granulator, and spray 10-20 ml of alcohol or solvent gasoline every 3-5 minutes to moisten the material, so that the material adheres, and after the granulator rotates for 30 minutes, pass through a 100-mesh sieve to obtain a molybdenum-copper mixed spherical material; S4, spreading the molybdenum-copper mixed spherical material on a corundum crucible, placing it in a heating furnace and heating it to 600-800° C., and pre-sintering it for 1-1.5 hours under a hydrogen protective atmosphere to obtain a prefabricated nearly spherical molybdenum-copper alloy powder; S5, performing electron beam remelting additive manufacturing on the prefabricated nearly spherical molybdenum-copper alloy powder to print a molybdenum-copper alloy; S6. Cut the molybdenum-copper alloy from the substrate using wire cutting equipment, and perform sandblasting on the molybdenum-copper alloy to remove excess metal material on the surface of the blank.
[0007] The present invention is also characterized in that: The average particle size of the electrolytic pure copper powder in S1 is 5~15 microns, and the average particle size of the pure molybdenum powder is 5~10 microns. Calculated by mass percentage, the content of electrolytic pure copper powder in the mixed powder is 40%~20%, and the content of molybdenum powder is 60~80%.
[0008] The ball-to-material ratio during grinding in S2 is 5:1. The grinding balls are pure molybdenum balls with a diameter of 3 to 8 mm. The rotation speed is 800 to 1000 rpm. Nitrogen or argon is used as a protective atmosphere during the grinding process to fill the grinding tank. The atmosphere is replaced every half an hour.
[0009] The specific process parameters in S3 are: the ground powder is sprinkled at a flow rate of 3 to 5 liters / minute from a height of 30 to 50 cm from the disc granulator, and the rotation speed of the disc granulator is 20 to 50 revolutions / minute.
[0010] The hydrogen flow rate in S4 is 20~30 liters / hour.
[0011] The specific method of S5 is: S5.1. Take the prefabricated nearly spherical molybdenum-copper alloy powder and place it in the material box of the electron beam remelting device. Vacuum it so that the pressure inside the material box is 4~8×10 -3 Pa; S5.2. Preheat the stainless steel or ceramic substrate of the electron beam 3D printing equipment, and control the preheating temperature at 500-650°C; S5.3, set the electron beam melting process parameters: print electron beam spot 50~70μm, excitation voltage 50~70Kv, scan current 10~20mA, print speed 0.8m / s, scan spacing 50~100pm; S5.4. Start printing under the set process parameters, and use the powder feeding device to spread the prefabricated nearly spherical molybdenum-copper alloy powder obtained in S4 on the substrate with a thickness of 0.1~0.3mm. Use electron beam melting printing with set parameters. After each layer is printed, the platform moves down one layer, and the powder spreading device starts working again. The powder spreading thickness is still maintained at 0.1~0.3mm. After the powder spreading is completed, electron beam melting printing is performed; repeat the above powder spreading and powder feeding operations until the preset thickness of the blank is reached to obtain the molybdenum-copper alloy.
[0012] The amount of nearly spherical molybdenum-copper alloy powder in S5.1 is determined according to the weight of the printed part, specifically 3 kg more than the weight of the printed part.
[0013] The specific sandblasting treatment of the molybdenum-copper alloy in S6 is as follows: 80-mesh brown corundum sand shots are used, the sandblasting pressure is 0.5-0.6 MPa, and the sandblasting time is 3-5 min.
[0014] The beneficial effects of the present invention are: (1) The method for preparing molybdenum-copper composite materials based on additive manufacturing of the present invention adopts mechanical alloying + granulation to prepare electron beam melted molybdenum-copper alloy powder. The process is simple, and the alloy powder obtained in large quantities has high sphericity and uniform particle size, which meets the raw material requirements of subsequent additive manufacturing and saves costs; (2) The present invention is a method for preparing a molybdenum-copper composite material based on additive manufacturing. The molybdenum-copper composite material is prepared by electron beam melting additive manufacturing technology. The molybdenum-copper composite material is melted layer by layer, and there is no component segregation due to the large difference in melting points, wettability, and solubility between molybdenum and copper. As a result, the two phases are metallurgically combined and evenly distributed, with extremely high density. (3) The molybdenum-copper composite material (generally Mo60Cu40, Mo70Cu30, Mo80Cu20) prepared by the method for preparing molybdenum-copper composite material based on additive manufacturing of the present invention has a density of more than 99.7% and a thermal conductivity of more than 210W / (m·K), which is not only beneficial to improve its thermal conductivity, but also can obtain any shape and higher comprehensive performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 It is a schematic structural diagram of a granulation device used in the method for preparing a molybdenum-copper composite material based on additive manufacturing of the present invention; Figure 2 This is a microscopic photograph of spherical molybdenum-copper composite powder prepared by the method for preparing molybdenum-copper composite materials based on additive manufacturing of the present invention. DETAILED DESCRIPTION
[0016] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0017] Method for preparing molybdenum-copper composite materials based on additive manufacturing, using Figure 1 The granulation device shown is completed, and the specific steps are as follows: S1. Raw material selection and proportion: electrolytic pure copper and pure molybdenum powder are mixed to obtain mixed powder; The average particle size of the electrolytic pure copper powder is 5~15 microns, and the average particle size of the pure molybdenum powder is 5~10 microns. According to user needs, the two powders are mixed in mass percentage. The content of electrolytic pure copper powder in the mixed powder is 40%~20%, and the content of molybdenum powder is 60~80%.
[0018] S2, mechanical alloying grinding: grinding the mixed powder with grinding balls for 2-5 hours to obtain grinding powder; The ball-to-material ratio during grinding is 5:1. The grinding balls are pure molybdenum balls with a diameter of 3 to 8 mm. The rotation speed is 800 to 1000 rpm. Nitrogen or argon is used as a protective atmosphere during the grinding process to fill the grinding jar. The atmosphere is replaced every half an hour.
[0019] S3, granulation: the ground powder is sprinkled at a flow rate of 3-5 liters / minute from a height of 30-50 cm from the disc granulator, the rotation speed of the disc granulator is 20-50 rpm, and 10-20 ml of alcohol or solvent gasoline is sprayed every 3-5 minutes to wet the material so that the material adheres. After the granulator rotates for 30 minutes, it passes through a 100-mesh sieve to obtain a molybdenum-copper mixed spherical material; S4, pre-sintering: Spread the molybdenum-copper mixed spherical material on a corundum crucible, place it in a heating furnace and heat it to 600-800°C, and pre-sinter it for 1-1.5 hours under a hydrogen protective atmosphere, wherein the hydrogen flow rate is 20-30 liters / hour, to obtain a prefabricated nearly spherical molybdenum-copper alloy powder; S5. Electron beam remelting additive manufacturing: The prefabricated nearly spherical molybdenum-copper alloy powder is subjected to electron beam remelting additive manufacturing to print the molybdenum-copper alloy; the specific method is as follows: S5.1. Take the prefabricated nearly spherical molybdenum-copper alloy powder and place it in the material box of the electron beam remelting device. The amount of nearly spherical molybdenum-copper alloy powder is determined according to the weight of the printed part, specifically 3 kg more than the weight of the printed part. The material box is vacuumed so that the internal pressure of the material box is 4~8×10 -3 Pa; S5.2. Preheat the stainless steel or ceramic substrate of the electron beam 3D printing equipment, and control the preheating temperature at 500-650°C; S5.3, set the electron beam melting process parameters: print electron beam spot 50~70μm, excitation voltage 50~70Kv, scan current 10~20mA, print speed 0.8m / s, scan spacing 50~100pm; S5.4. Start printing under the set process parameters, and use the powder feeding device to spread the prefabricated nearly spherical molybdenum-copper alloy powder obtained in S4 on the substrate with a thickness of 0.1~0.3mm. Use electron beam melting printing with set parameters. After each layer is printed, the platform moves down one layer, and the powder spreading device starts working again. The powder spreading thickness is still maintained at 0.1~0.3mm. After the powder spreading is completed, electron beam melting printing is performed; repeat the above powder spreading and powder feeding operations until the preset thickness of the blank is reached to obtain the molybdenum-copper alloy.
[0020] S6. Cutting the printed body: Use wire cutting equipment to cut the molybdenum-copper alloy from the substrate, and perform sandblasting on the molybdenum-copper alloy to remove excess metal material on the surface of the body. Specifically, use 80-mesh brown corundum sand shots, the sandblasting pressure is 0.5-0.6 MPa, and the sandblasting time is 3-5 min.
[0021] The present application uses additive manufacturing technology to prepare metal-based materials. Currently, spherical powders are mostly used, and the preparation of spherical powders mostly uses atomization. For composite materials, several components must be able to dissolve in each other to form alloys or other compounds, otherwise it is difficult to form a molten liquid, and then cut, crack, and cool it into a spherical powder. The present invention is aimed at molybdenum and copper, two metals with extremely different melting points, almost no solubility in each other, and completely different properties. Therefore, it is impossible to prepare the corresponding alloys by smelting, and then it is impossible to prepare spherical powders by atomization. Therefore, the present invention adopts mechanical grinding, and then the ground ultrafine powder is rolled into a sphere by a homemade granulator. In order to improve the strength, a high-temperature pre-sintering method is adopted (the prepared spherical powder is as follows Figure 2 As shown in the figure), this spherical powder can be used to complete subsequent additive manufacturing.
[0022] Example 1 The method for preparing molybdenum-copper composite materials based on additive manufacturing, the specific steps are as follows: S1, mixing electrolytic pure copper and pure molybdenum powder to obtain mixed powder; The average particle size of the electrolytic pure copper powder is 5 microns, and the average particle size of the pure molybdenum powder is 5 microns. The content of the electrolytic pure copper powder in the mixed powder is 40%, and the content of the molybdenum powder is 60%.
[0023] S2, using pure molybdenum grinding balls with a diameter of 3 mm to grind the mixed powder for 3 h, the ball-to-material ratio is 5:1, the rotation speed is 1000 rpm, nitrogen is used as a protective atmosphere during the process, the grinding tank is filled, and the atmosphere is changed every half an hour to obtain ground powder; S3, the ground powder was sprinkled at a flow rate of 3 liters / minute from a height of 40 cm from the disc granulator, the rotation speed of the disc granulator was 20 rpm, and 10 ml of alcohol was sprayed every 3 minutes to wet the material, and the material was passed through a 100-mesh sieve after the granulator rotated for 30 minutes to obtain a molybdenum-copper mixed spherical material; S4, spreading the molybdenum-copper mixed spherical material on a corundum crucible, placing it in a heating furnace and heating it to 600° C., pre-sintering it for 1 hour under a hydrogen protective atmosphere, wherein the hydrogen flow rate is 30 liters / hour, to obtain a prefabricated nearly spherical molybdenum-copper alloy powder; S5. Electron beam remelting and additive manufacturing are performed on the prefabricated nearly spherical molybdenum-copper alloy powder to obtain a molybdenum-copper alloy by printing. The specific method is as follows: S5.1. Take the prefabricated nearly spherical molybdenum-copper alloy powder and place it in the material box of the electron beam remelting device. The amount of nearly spherical molybdenum-copper alloy powder is 3 kg more than the weight of the printed parts. Vacuum the material box so that the internal pressure of the material box is 4×10 -3 Pa; S5.2. Preheat the stainless steel or ceramic substrate of the electron beam 3D printing equipment, and control the preheating temperature at 600°C; S5.3, set the electron beam melting process parameters: print electron beam spot 50μm, excitation voltage 50Kv, scan current 10mA, print speed 0.8m / s, scan spacing 50pm; S5.4. Start printing under the set process parameters, and use the powder feeding device to spread the prefabricated nearly spherical molybdenum-copper alloy powder obtained in S4 on the substrate with a thickness of 0.3mm. Use electron beam melting printing with set parameters. After each layer is printed, the platform moves down one layer, and the powder spreading device starts working again. The powder spreading thickness remains at 0.3mm. After the powder spreading is completed, electron beam melting printing is performed; repeat the above powder spreading and powder feeding operations until the preset thickness of the blank is reached to obtain the molybdenum-copper alloy.
[0024] S6. Cut the molybdenum-copper alloy from the substrate using wire cutting equipment, use 80-mesh brown corundum sand shots, the blasting pressure is 0.5 MPa, and the blasting time is 5 min. Shot blast the molybdenum-copper alloy to remove excess metal material on the surface of the blank.
[0025] Example 2 The method for preparing molybdenum-copper composite materials based on additive manufacturing, the specific steps are as follows: S1. Mixing electrolytic pure copper powder with an average particle size of 10 microns and pure molybdenum powder with an average particle size of 8 microns to obtain a mixed powder, wherein the content of the electrolytic pure copper powder in the mixed powder is 30%, and the content of the molybdenum powder is 70%.
[0026] S2, using pure molybdenum grinding balls with a diameter of 8 mm to grind the mixed powder for 4 h, the ball-to-material ratio is 5:1, the rotation speed is 800 rpm, during the process, argon is passed as a protective atmosphere, the grinding tank is filled, and the atmosphere is replaced every half an hour to obtain ground powder; S3, the ground powder was sprinkled at a flow rate of 5 liters / minute from a height of 50 cm from the disc granulator, the rotation speed of the disc granulator was 40 rev / min, and 20 ml of gasoline was sprayed every 5 minutes to wet the material, and the material was passed through a 100-mesh sieve after the granulator rotated for 30 minutes to obtain a molybdenum-copper mixed spherical material; S4, spreading the molybdenum-copper mixed spherical material on a corundum crucible, placing it in a heating furnace and heating it to 700° C., pre-sintering it for 1.5 hours under a hydrogen protective atmosphere, wherein the hydrogen flow rate is 20 liters / hour, to obtain a prefabricated nearly spherical molybdenum-copper alloy powder; S5. Electron beam remelting and additive manufacturing are performed on the prefabricated nearly spherical molybdenum-copper alloy powder to obtain a molybdenum-copper alloy by printing. The specific method is as follows: S5.1. Take the prefabricated nearly spherical molybdenum-copper alloy powder and place it in the material box of the electron beam remelting device. The amount of nearly spherical molybdenum-copper alloy powder is 3 kg more than the weight of the printed parts. Vacuum the material box so that the internal pressure of the material box is 8×10 -3 Pa; S5.2. Preheat the stainless steel or ceramic substrate of the electron beam 3D printing equipment, and control the preheating temperature at 500°C; S5.3, set the electron beam melting process parameters: print electron beam spot 70μm, excitation voltage 60Kv, scan current 20mA, print speed 0.8m / s, scan spacing 80pm; S5.4. Start printing under the set process parameters, and use the powder feeding device to spread the prefabricated nearly spherical molybdenum-copper alloy powder obtained in S4 on the substrate with a thickness of 0.1mm. Use electron beam melting printing with set parameters. After each layer is printed, the platform moves down one layer, and the powder spreading device starts working again. The powder spreading thickness remains at 0.1mm. After the powder spreading is completed, electron beam melting printing is performed; repeat the above powder spreading and powder feeding operations until the preset thickness of the blank is reached to obtain the molybdenum-copper alloy.
[0027] S6. Cut the molybdenum-copper alloy from the substrate using wire cutting equipment, use 80-mesh brown corundum sand shots, the blasting pressure is 0.6 MPa, and the blasting time is 3 min. Shot blast the molybdenum-copper alloy to remove excess metal material on the surface of the blank.
[0028] Example 3 The method for preparing molybdenum-copper composite materials based on additive manufacturing, the specific steps are as follows: S1. Mixing electrolytic pure copper powder with an average particle size of 15 microns and pure molybdenum powder with an average particle size of 10 microns to obtain a mixed powder, wherein the content of the electrolytic pure copper powder in the mixed powder is 20%, and the content of the molybdenum powder is 80%.
[0029] S2, using pure molybdenum grinding balls with a diameter of 5 mm to grind the mixed powder for 5 h, the ball-to-material ratio is 5:1, the rotation speed is 900 rpm, during the process, argon is passed as a protective atmosphere, the grinding tank is filled, and the atmosphere is replaced every half an hour to obtain ground powder; S3, the ground powder was sprinkled at a flow rate of 4 liters / minute from a height of 30 cm from the disc granulator, the rotation speed of the disc granulator was 50 rev / min, and 18 ml of gasoline was sprayed every 4 minutes to wet the material, and the material was passed through a 100-mesh sieve after the granulator rotated for 30 minutes to obtain a molybdenum-copper mixed spherical material; S4, spreading the molybdenum-copper mixed spherical material on a corundum crucible, placing it in a heating furnace and heating it to 800° C., pre-sintering it for 1.5 hours under a hydrogen protective atmosphere, wherein the hydrogen flow rate is 25 liters / hour, to obtain a prefabricated nearly spherical molybdenum-copper alloy powder; S5. Electron beam remelting and additive manufacturing are performed on the prefabricated nearly spherical molybdenum-copper alloy powder to obtain a molybdenum-copper alloy by printing. The specific method is as follows: S5.1. Take the prefabricated nearly spherical molybdenum-copper alloy powder and place it in the material box of the electron beam remelting device. The amount of nearly spherical molybdenum-copper alloy powder is 3 kg more than the weight of the printed parts. The material box is vacuumed so that the internal pressure of the material box is 6×10 -3 Pa; S5.2. Preheat the stainless steel or ceramic substrate of the electron beam 3D printing equipment, and control the preheating temperature at 650°C; S5.3, set the electron beam melting process parameters: print electron beam spot 60μm, excitation voltage 70Kv, scan current 20mA, print speed 0.8m / s, scan spacing 100pm; S5.4. Start printing under the set process parameters, and use the powder feeding device to spread the prefabricated nearly spherical molybdenum-copper alloy powder obtained in S4 on the substrate with a thickness of 0.2mm. Use electron beam melting printing with set parameters. After each layer is printed, the platform moves down one layer, and the powder spreading device starts working again. The powder spreading thickness remains at 0.2mm. After the powder spreading is completed, electron beam melting printing is performed; repeat the above powder spreading and powder feeding operations until the preset thickness of the blank is reached to obtain the molybdenum-copper alloy.
[0030] S6. Cut the molybdenum-copper alloy from the substrate using wire cutting equipment, use 80-mesh brown corundum sand shots, the blasting pressure is 0.6 MPa, and the blasting time is 3 min. Shot blast the molybdenum-copper alloy to remove excess metal material on the surface of the blank.
Claims
1. A method for preparing a molybdenum-copper composite material based on additive manufacturing, characterized in that: The specific steps are as follows: S1, mixing electrolytic pure copper and pure molybdenum powder to obtain mixed powder; S2, grinding the mixed powder with grinding balls for 2-5 hours to obtain ground powder; S3, sprinkle the ground powder from a height above the disc granulator, and spray 10-20 ml of alcohol or solvent gasoline every 3-5 minutes to moisten the material, and after the granulator rotates for 30 minutes, pass through a 100-mesh sieve to obtain a molybdenum-copper mixed spherical material; S4, spreading the molybdenum-copper mixed spherical material on a corundum crucible, placing it in a heating furnace and heating it to 600-800° C., and pre-sintering it for 1-1.5 hours under a hydrogen protective atmosphere to obtain a prefabricated nearly spherical molybdenum-copper alloy powder; S5, performing electron beam remelting additive manufacturing on the prefabricated nearly spherical molybdenum-copper alloy powder to print a molybdenum-copper alloy; S6. Cut the molybdenum-copper alloy from the substrate using wire cutting equipment, and perform sandblasting on the molybdenum-copper alloy to remove excess metal material on the surface of the blank.
2. The method for preparing a molybdenum-copper composite material based on additive manufacturing according to claim 1, characterized in that: The average particle size of the electrolytic pure copper powder in S1 is 5-15 microns, and the average particle size of the pure molybdenum powder is 5-10 microns. In terms of mass percentage, the content of the electrolytic pure copper powder in the mixed powder is 40%-20%, and the content of the molybdenum powder is 60-80%.
3. The method for preparing a molybdenum-copper composite material based on additive manufacturing according to claim 1, characterized in that: The ball-to-material ratio during grinding in S2 is 5:
1. The grinding balls are pure molybdenum balls with a diameter of 3 to 8 mm, and the rotation speed is 800 to 1000 rpm. Nitrogen or argon is used as a protective atmosphere during the grinding process to fill the grinding jar, and the atmosphere is replaced every half an hour.
4. The method for preparing a molybdenum-copper composite material based on additive manufacturing according to claim 1, characterized in that: The specific process parameters in S3 are: the ground powder is sprinkled at a flow rate of 3 to 5 liters / minute from a height of 30 to 50 centimeters from the disc granulator, and the rotation speed of the disc granulator is 20 to 50 revolutions / minute.
5. The method for preparing a molybdenum-copper composite material based on additive manufacturing according to claim 1, characterized in that: The hydrogen flow rate in S4 is 20-30 liters / hour.
6. The method for preparing a molybdenum-copper composite material based on additive manufacturing according to claim 1, characterized in that: The specific method of S5 is: S5.
1. Take the prefabricated nearly spherical molybdenum-copper alloy powder and place it in the material box of the electron beam remelting device. Vacuum it so that the pressure inside the material box is 4~8×10 -3 Pa; S5.
2. Preheat the stainless steel or ceramic substrate of the electron beam 3D printing equipment, and control the preheating temperature at 500-650°C; S5.3, set the electron beam melting process parameters: print electron beam spot 50~70μm, excitation voltage 50~70Kv, scan current 10~20mA, print speed 0.8m / s, scan spacing 50~100pm; S5.
4. Start printing under the set process parameters, and use the powder feeding device to spread the prefabricated nearly spherical molybdenum-copper alloy powder obtained in S4 on the substrate with a thickness of 0.1~0.3mm. Use electron beam melting printing with set parameters. After each layer is printed, the platform moves down one layer, and the powder spreading device starts working again. The powder spreading thickness is still maintained at 0.1~0.3mm. After the powder spreading is completed, electron beam melting printing is performed; repeat the above powder spreading and powder feeding operations until the preset thickness of the blank is reached to obtain the molybdenum-copper alloy.
7. The method for preparing a molybdenum-copper composite material based on additive manufacturing according to claim 6, characterized in that: The amount of the nearly spherical molybdenum-copper alloy powder in S5.1 is determined according to the weight of the printed part, specifically 3 kg more than the weight of the printed part.
8. The method for preparing a molybdenum-copper composite material based on additive manufacturing according to claim 1, characterized in that: The sandblasting treatment of the molybdenum-copper alloy in S6 is specifically performed by using 80-mesh brown corundum sand shots, a sandblasting pressure of 0.5-0.6 MPa, and a sandblasting time of 3-5 min.
Citation Information
Patent Citations
Method for high-speed laser cladding of Mo-Cu alloy layer on copper substrate
CN112708882A
Mo-Cu alloy preparation method based on surface coating technology and flame spraying technology
CN115710683A
